Game changer? A sporting indication to implant a left atrial appendage closure device in a rugby player with atrial fibrillation: a case report. Issue 1 (29th January 2020) - Briosa e Gala, Andre; Cox, Andrew; Pope, Michael; Betts, Timothy
Abstract: Background: Caring for athletes with cardiac disease requires an approach that caters to the specific needs of the athlete. Case summary: A 27-year-old professional rugby player was admitted with decompensated heart failure and atrial fibrillation (AF). Transthoracic echocardiogram showed features in keeping with a dilated cardiomyopathy with severe left ventricular (LV) systolic impairment. He made good progress on evidence-based heart failure medication and his LV systolic function returned to normal. He failed to maintain sinus rhythm with cardioversion and remained in persistent AF. He then suffered a transient ischaemic attack despite appropriate anticoagulation. At 1-year follow-up, he was asymptomatic and against medical advice continued to play competitive rugby whilst taking rivaroxaban. He subsequently underwent implantation with a percutaneous left atrial appendage occlusion device, allowing him to discontinue anticoagulation, reduce his bleeding risk and resume his career, whilst simultaneously lowering the thromboembolic risk. Discussion: Counselling should include different management options aimed at minimizing the risks to athletes if they to return to competitive sports. Left atrial appendage occlusion devices are a suitable AF-related stroke prevention strategy in athletes competing in full-contact sports.